DINAMIKA PELAYANAN REMAJA DAN PEMUDA KRISTENPERAN STRATEGIS GEMBALA DALAM MENGINSPIRASI DAN MEMBIMBING - Munthe, Denyka; Alexander Sumampouw (STT-RAI Batam, 2024)
In the changing times that continue to develop, ministry to Christian teenagers and youth is becoming increasingly important for the Church. The dynamics of youth and youth ministry are increasingly fading, teenagers are no longer interested in serving or even coming to worship. This research highlights the strategic role of pastors in guiding and inspiring the younger generation regarding the difficulties they face in accordance with Christian values. Through a deep understanding of the dynamics of youth and youth ministry, as well as relevant strategies, it is hoped that the Church can be more effective in guiding the younger generation to face today's challenges. With awareness of the pastor's strategy, it is hoped that the Church can build a young generation that is strong and relevant to the times.